Preparation of hybrid CuO/TiO₂ photocatalyst responsive towards UV-light (effect of incubation time) - Shanan, Nur Syuhada; Lim, Ying Pei; Lim, Ying Chin (2017)
Titanium dioxide (TiO₂) photocatalyst is one of the promising methods used in the treatment of dye removals. However, it has to be doped with other metals such copper oxide (CuO) to increase the efficiency, reactivity and stability under UV-light. This study was carried out to prepare hybrid CuO/TiO₂ using wet impregnation method by varying the incubation times at 1, 2, 4, 8 and 24 hr as well as to evaluate the photocatalytic removal of methyl orange under UV-light irradiation by hybrid CuO/TiO₂ photocatalyst. Then, characterization of the photocatalyst was done by XRD, EDX, FESEM and BET analysis. Hybrid photocatalyst sample was prepared using Copper (II) acetate monohydrate as the precursor for copper loading at a condition of 0.5wt%, 50˚C and various incubation times. Photocatalytic degradation for 10 ppm of methyl orange was studied under UV-light irradiation and the extent of dye degradation was determined using UV-Vis Spectrophotometer. Thus, from the research, the result showed that the sample being incubated at 2 hr during preparation of hybrid photocatalyst is an optimal result as it showed the best decolourization results with 82.06% of methyl orange removal.